Is binning always sinning? The impact of time-averaging for exoplanet phase curves. Issue 2 (4th October 2022) - Morello, Giuseppe; Dyrek, Achrène; Changeat, Quentin
ABSTRACT: We explore how finite integration time or temporal binning can affect the analysis of exoplanet phase curves. We provide analytical formulae to account for this effect or, if neglected, to estimate the potential biases in the retrieved parameters. As expected, due to their smoother variations over longer time-scales, phase curves can be binned more heavily than transits without causing severe biases. In the simplest case of a sinusoidal phase curve with period P, the integration time Δ t reduces its amplitude by the scaling factor sinc(πΔ t / P ), without altering its phase or shape. We also provide formulae to predict reasonable parameter error bars from phase-curve observations. Our findings are tested with both synthetic and real data sets, including unmodelled astrophysical signals and/or instrumental systematic effects. Tests with the Spitzer data show that binning can affect the best-fitting parameters beyond predictions, due to the correction of high-frequency correlated noise. Finally, we summarize key guidelines for speeding up the analysis of exoplanet phase curves without introducing significant biases in the retrieved parameters.